A Cantonese voluntary association: A case study of Sam Sui Wui Kwoon in Malacca / Loh Chew Boon - Loh , Chew Boon (1985)
This research project is a study of the of the Sam Sui Wui Kwoon in Malacca, i.e. a Cantonese clan association. The main purpose is to get a clearer insight into the position of the association in Malacca today and to look into the progress/development or decline of the activities of the association. I begin this graduation by discussing the objective and scope of the research and difficulties encountered in the course of the fieldwork, the basic concept of a voluntary association and the origin of Chinese association. A short history of the establishment of the Chinese voluntary associations in Malaysia and also their functions at the time are also dealt with in this chapter. Kenneth Little’s findings on West African voluntary association are summarized here and put forward for application in the Malaysian context with special reference to Sam Sui Wui Kwoon. The second chapter touches on some of the pertinent issues pertaining to the Sam Sui Wui Kwoon. The historical background of the humble beginnings of Sam Sui Wui Kwoon are presented. Apart form that, the objective, constitution and regulations, organisation and financial standing of the association are also explained at full length. The present stage of Sam Sui Wui Kwoon with regards to its activities, functions and membership is discussed and elaborated in chapter III. Following this, the fourth chapter encumbers part of the field findings and attempts is made to evaluate the present status, functions and membership of the Sam Sui Wui Kwoon. The opinions of the respondents especially with regards to the reasons for their non-membership are presented here. In comparison, the activities of wether or not Kenneth Little’s conclusion regarding the voluntary associations in West Africa is applicable in a Malaysian context. At the end of this last chapter, I forward some suggestions to improve the Sam Sui Wui Kwoon.